Summary of hybrid learning microcourse modules and training material - Diaz Espinosa, Anabell Guadalupe; Torres Mota, Suelen Yajaira; Estrada Estrada, Juan Antonio; García Santiago, Jorge Octavio; Ovando, Rausel; Van Loon, Jelle (CIMMYT, 2025)
During 2025, three strategic capacity-building material developments were strengthened and expanded to support farmers and field technicians across Latin America. These efforts responded to the need for more accessible, flexible, and context-relevant learning options for rural communities. The initiative aimed to reduce the gap between available knowledge and the practical skills required to address the challenges of modern agriculture by combining digital innovation, field-applicable content, and inclusive approaches that consider diverse learner profiles and connectivity limitations. The first development focused on the continued design and dissemination of digital micro-courses through AgroTutor Academy, a decentralized platform that enables partner organizations to create and deliver WhatsApp-based courses in an efficient and scalable way. Implemented as a self-paced, distance learning experience using automated responses, these micro-courses supported farmers and technicians in building foundational digital skills, helping participants recognize the benefits of technology in their agricultural context and strengthening their ability to adopt digital tools in practice. In parallel, instructional materials were developed for two technical micro-courses: Water Management: Fundamentals for Farmers and Introduction to Regenerative Agriculture which were tested and refined during the last quarter of the year. These courses aimed to improve decision-making around efficient water use and promote regenerative agriculture principles as a sustainable production approach. Finally, progress was made on the integrated multilingual edition of the InnovaHub Essential Tools guide in Spanish, Maya (Mayat’aan), and English, reinforcing CIMMYT’s institutional commitment to inclusion, equity, and cultural relevance in knowledge dissemination. This multilingual compendium seeks to serve as a bridge between scientific knowledge, local practices, and field implementation, expanding access to innovation tools and methodologies for diverse stakeholders. Complementing these materials, the Regenerative Agriculture Diploma Program was designed as a comprehensive 100-hour training pathway structured into four modules (Introduction, Water, Soil, and Biodiversity), aimed at strengthening the capacities needed to transition toward more sustainable, resilient, and socially just agricultural systems.